OPTIMASI JARAK TANAM DAN PEMUPUKAN NITROGEN UNTUK PERTUMBUHAN DAN PRODUKSI UMBI MINI BAWANG MERAH (Allium ascalonicum) ASAL TSS - Fajar Risqi Yuniarti; Syaiful Anwar; Karno Karno (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2022)
Growing shallot from true shallot seed (Allium ascalonicum) is an alternative method. The aim of the experiment was to examine the effects of plant spacing and nitrogen fertilizer on the growth and production of shallot from TSS and the interaction between the treatments. The experimental design of this study was a Randomized Block Design (RBD) factorial 3x3 with 3 replications. The first factor was plant spacing, with 3 levels, 5 cm x 10 cm; 7,5 cm x 10 cm; and 10 cm x 10 cm. The second factor was nitrogen fertilizer, with 3 levels of dosage: 45 kg/ha, 90 kg/ha, and 135 kg/ha. The observed parameters were plant height, number of leaves per plot, bulb diameter, number of bulbs per plot, bulb fresh weight per plot, bulb dry weight per plot (sunlight), and bulb dry matter per plot (oven). Data was analyzed with the F test and HSD at 5%. The result showed that plant spacing affected bulb diameter, number of bulbs per plot, bulb fresh weight per plot, and bulb dry weight per plot (sunlight). Nitrogen fertilizer application only increased the number of leaves per plot. On all observed parameters, there was no interaction between plant spacing and nitrogen fertilizer application